Modeling and analysis of new types of electrochemical components : solid oxide fuel cell (SOFC) and vanadium redox flow battery (VRB) for system level application - Zhang, Yu (2016)
With the prosperous development of distributed power grid and renewable electrical sources, new type of electrochemical components have received the most attention to date for their high efficiency and low pollution. Among all kinds of electrochemical components, vanadium redox flow batteries (VRB) and solid oxide fuel cell (SOFC) are especially suited for large-scale electrical storage and generation correspondingly. However, so far, there are rare models of SOFC and VRB for system-level analysis. This thesis aims to develop the methodologies for SOFC and VRB modeling which are concise and reliable under different operating conditions. Moreover, several novel plant structures are studied based on the proposed models of SOFC and VRB. At the beginning, two SOFC models, namely, a simplified 1D distributed model and a theoretical lumped model are established for thermal analysis and electrical analysis correspondingly. The form of both models are simplified and verification shows that both SOFC models are accurate. Then, based on the proposed distributed model of SOFC, a novel temperature-maintained SOFC combine gas turbine hybrid plant (SOFC-GT) is built up. Through introducing a heat management subsystem, the average temperature of SOFC can be adjusted by controlling the volume of GT’s exhaust and additional fuel. Besides, based on different air and fuel supply patterns, an optimal partial-load strategy of the proposed plant is found out. On the other hand, based on experimental data, a comprehensive electrical circuit model of VRB is identified by using least square method. The inherent features of flow battery such as shunt current, ion diffusion and pumping energy consumption are considered. The identification model of VRB is suited for power grid analysis due to its straightforward form and favorable accuracy. Finally, a novel DC grid composed of SOFC, VRB and super-capacitor (SC) is proposed to solve the lack of electricity in remote areas. Based on the proposed lumped model of SOFC and identification model of VRB, the novel hybrid DC grid is simulated.